2022
DOI: 10.3390/ph15121468
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Effect of Neuroaid® on Strychnine-Induced Convulsions in Mice

Abstract: NeuroAid II, a folk Chinese Medicine, is currently used in Asia for the treatment of stroke. An experimental study demonstrated that NeuroAid enables neuronal cells to be more resistant to glutamate toxicity. This research was constructed to evaluate the efficacy of NeuroAid in the prevention of epilepsy (EP). Forty healthy adult male mice were used and divided into four groups (10 mice/group): normal control group; positive control group; NeuroAid-treated group (10 mg/kg); topiramate-treated group (10 mg/kg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In this study, we found that cleaved caspase-3 and BAX were increased in the kidneys of mice in the glycerol group, as observed in another study [ 29 , 30 ] but significantly decreased in the mice treated with citronellol in both low and high doses. This suggests that treatment with citronellol may reduce apoptosis in the kidneys of mice.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that cleaved caspase-3 and BAX were increased in the kidneys of mice in the glycerol group, as observed in another study [ 29 , 30 ] but significantly decreased in the mice treated with citronellol in both low and high doses. This suggests that treatment with citronellol may reduce apoptosis in the kidneys of mice.…”
Section: Discussionsupporting
confidence: 88%
“…However, exceeding the recommended dosage may lead to infrequent yet severe side effects such as hepatotoxicity [ 26 ]. Its use is associated with certain limitations, such as the potential for nausea, vomiting, electrolyte imbalances, hemolytic anemia, and neurotoxicity [ 27 ]. Nephrotoxicity is a grave concern, being the primary dose-limiting adverse effect of cisplatin [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation has been associated with neurological conditions and damage to the CNS induced by neurotoxicants [ 18 ]. Inflammatory mediators such as TNF-α and nuclear factor-κB (NF-κB) are crucial in the formation of neuroinflammation following chemotherapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%